Brief Analysis of the Value of PVI in Guiding Anesthesia Volume Management for Preeclampsia Patients Undergoing Cesarean Section - Wang, Dawei (International Journal of Public Health and Medical Research, 2025)
As a non-invasive and dynamic blood volume monitoring technology, the application value of PVI (Peripheral Vascular Index) in cesarean section for preeclampsia patients has received attention. This study adopted a prospective randomized controlled trial, enrolling 120 preeclampsia patients who underwent cesarean section, and were randomly assigned to receive either PVI-guided volume management or traditional volume management. The results showed that PVI-guided volume management effectively reduced the incidence of intraoperative hypotension, decreased fluid intake, and increased urine output. Additionally, it improved the Apgar score and umbilical artery blood pH value of newborns, optimizing maternal and fetal outcomes. PVI allowed for real-time assessment of blood volume changes, making volume management more precise and enhancing perioperative hemodynamic stability. The study results indicate that PVI has high clinical application value in anesthesia management for preeclampsia patients. Future large-scale, multi-center studies are needed to optimize perioperative volume management strategies, improve surgical safety, and enhance prognosis quality.